Are large firms more profitable than small and medium firms in the European Union? - Gaio, Cristina (2018)
This study comparatively analyses the profitability between large enterprises (LE) and small and medium enterprises (SME) in the European Union in order to understand which group of companies is more profitable. The analysis is also segmented by groups of countries and industries. Furthermore, we study the impact of the financial crisis on profitability. The sample includes 54,654 firms from 21 EU countries and from 17 industries during the period between 2004 and 2013. Two measures of profitability are used: (1) Return on Assets (computed both with earnings before interest and taxes and net profit), and; (2) Return on Equity. The results suggest that LE are, on average, more profitable than SME. This finding holds across all industries except one. However, there is additional evidence that SME in Eastern Europe are more profitable than LE and are also more profitable than SME in Western Europe. Finally, the results also suggest that the financial crisis negatively impacted firms’ profitability, particularly in SME.